2013
DOI: 10.1002/jame.20016
|View full text |Cite
|
Sign up to set email alerts
|

Arctic sea‐ice evolution as modeled by Max Planck Institute for Meteorology's Earth system model

Abstract: [1] We describe the evolution of Arctic sea ice as modeled by the Max Planck Institute for Meteorology's Earth System Model (MPI-ESM). The modeled spatial distribution and interannual variability of the sea-ice cover agree well with satellite observations and are improved relative to the model's predecessor ECHAM5/MPIOM. An evaluation of modeled sea-ice coverage based on sea-ice area gives, however, conflicting results compared to an evaluation based on sea-ice extent and is additionally hindered by uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(149 citation statements)
references
References 49 publications
10
137
0
2
Order By: Relevance
“…This sensitivity of coupled ice-ocean models to the atmospheric forcing dataset was also found by both Hunke and Holland (2007) and Notz et al (2013). In the Notz et al (2013) study, the simulated September ice volume was less than half as much using ERA-Interim forcing compared to using NCEP-R1 forcing in part because the model was not fully adjusted to the different biases of each dataset. As a result the trend in September ice volume was also very different, 22.6 3 10 3 km 3 decade 21 for the NCEP-R1 forcing compared to a much weaker trend in the run with thinner ice, 21.6 3 10 3 km 3 decade 21 for the ERA-Interim forcing.…”
Section: Forcing An Ice-ocean Modelmentioning
confidence: 57%
See 2 more Smart Citations
“…This sensitivity of coupled ice-ocean models to the atmospheric forcing dataset was also found by both Hunke and Holland (2007) and Notz et al (2013). In the Notz et al (2013) study, the simulated September ice volume was less than half as much using ERA-Interim forcing compared to using NCEP-R1 forcing in part because the model was not fully adjusted to the different biases of each dataset. As a result the trend in September ice volume was also very different, 22.6 3 10 3 km 3 decade 21 for the NCEP-R1 forcing compared to a much weaker trend in the run with thinner ice, 21.6 3 10 3 km 3 decade 21 for the ERA-Interim forcing.…”
Section: Forcing An Ice-ocean Modelmentioning
confidence: 57%
“…Additionally, Notz et al (2013) found much different mean sea ice volume and volume trends in the Max Planck Institute Earth System Model using NCEP-R1 or ECMWF Interim Re-Analysis (ERA-Interim) forcing. These studies illustrate how important it is to consider the relative merits of reanalysis datasets for forcing an ice-ocean model.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The LIM models have a distinct cold bias in the North Atlantic and in the Greenland Sea. These cold biases are related to the common atmospheric ERA-Interim-based forcing, which is known to have a cold anomaly over the Fram Strait-Svalbard region (Notz et al, 2013). In the Norwegian and Barents Seas, LIM models' surfaces are warmer than PHC3, while their differences to WOA13 are relatively small.…”
Section: Arctic Surface Temperaturementioning
confidence: 98%
“…Virtually all modern sea ice models use either the VP or EVP formulation, combined with a thermodynamics model (e.g. Semtner, 1976;Bitz and Lipscomb, 1999;Vancoppenolle et al, 2009;Turner and Hunke, 2015) and variously detailed subgrid-scale parameterisations (for commonly used large-scale sea ice models as for instance CICE , LIM3 (Vancoppenolle et al, 2009), MITgcm (Adcroft et al, 2016) or MPI-ESM (Notz et al, 2013)). …”
Section: P Rampal Et Al: Nextsim: a New Lagrangian Sea Ice Modelmentioning
confidence: 99%